Akt-Fas to Quell Aberrant T Cell Differentiation and Apoptosis in Covid-19 - Leonardi, Anthony J.; Proenca, Rui B. (Frontiers in Immunology, 2020)
Aberrant T cell differentiation and lymphopenia are hallmarks of severe COVID-19 disease. Since T cells must race to cull infected cells, they are quick to differentiate and achieve cytotoxic function. With this responsiveness, comes hastened apoptosis, due to a coupled mechanism of death and differentiation in both CD4+ and CD8+ lymphocytes via CD95 (Fas) and serine-threonine kinase (Akt). T cell lymphopenia in severe cases may represent cell death or peripheral migration. These facets depict SARS-Cov-2 as a lympho-manipulative pathogen; it distorts T cell function, numbers, and death, and creates a dysfunctional immune response. Whether preservation of T cells, prevention of their aberrant differentiation, and expansion of their population may alter disease course is unknown. Its investigation requires experimental interrogation of the linked differentiation and death pathway by agents known to uncouple T cell proliferation and differentiation in both CD4+ and CD8+ T cells.